Low back pain: A rare presentation of Klebsiella pneumoniae liver abscess - Yu-Chen Tseng; Yu-Cheng Wu; Sheng-Kang Chiu; Ching-Hui Hsu (Journal of Medical Sciences, 2015)
Pyogenic liver abscess (PLA) is a global emerging infectious disease. The common presentations of PLA include fever, abdominal pain, anorexia, weight loss, and malaise. In Taiwan, Klebsiella pneumoniae is the most frequently isolated pathogen from PLA. Most cases of K. pneumoniae liver abscess (KLA) develop metastatic infections at other sites that cause severe complications, such as endophthalmitis, meningitis, or brain abscess. Herein, we describe a case of KLA that unusually presented as lower back pain. The patient received antibiotic therapy and underwent drainage procedure. He was eventually discharged in a stable condition, without any complications caused by the metastatic infections.